Teaching and Learning In Digital Technology Era: Method, Material Design and Media - Siregar, Roswani; Heni Subagiharti; Diah Syafitri Handayani; Dermawan Hutagaol; Efendi Barus (International Journal of Educational Research Excellence (IJERE), 2025)
This study presents a systematic literature review focusing on learning models, strategies, and the design of digital teaching materials in the context of education in the digital era. Drawing from 38 peer-reviewed articles published between 2018 and 2023, the research explores how digital technology has transformed pedagogical practices. The analysis reveals a strong emphasis on student-centered learning models, where students actively construct knowledge and develop problem-solving skills, rather than passively receiving information. Learning strategies such as problem-based, project-based, and research-based learning are widely promoted to foster critical thinking, creativity, communication, and collaboration. A key finding is the increasing adoption of blended learning, which combines face-to-face instruction with online platforms, thereby supporting more flexible and interactive educational experiences. However, the success of these strategies heavily depends on educators’ digital literacy, especially their competence in integrating technology with pedagogy and content. The design of digital teaching materials must also be aligned with learning objectives and students' needs. Effective materials incorporate diverse formats, such as infographics, videos, podcasts, and virtual labs, and are grounded in principles of relevance, consistency, and adequacy. The study concludes that digital pedagogy is becoming more widely implemented in Indonesia’s educational landscape. To ensure its effectiveness, educators must be equipped with adequate ICT skills, supported by proper infrastructure, and encouraged to collaborate with students for continuous improvement. With the right approach, digital technology can enhance educational outcomes, promote lifelong learning, and respond to the evolving needs of students in a technology-driven society